DAMPAK PERUBAHAN IKLIM TERHADAP PRODUKSI JAMBU METE DAN UPAYA PENANGGULANGANNYA - Supriadi, Handi; Heryana, Nana (Jurnal Tanaman Industri dan Penyegar, 2011)
Impact of climate change on cashew production and efforts of countermeasures. Climate change occurs due to the increasing content of greenhouse gases (GHGs)  in the air, mostly resulting from the rapidly growing industrialization. As a result of climate change causes: (1) the earths temperature increased, (2) extreme climate events (climatic anomalies) increased, as events Enso (El-Nino that caused drought and La-Nina causes floods), (3) a decrease and an increase air temperature extremes, (4) changes in rainfall patterns and (5) rise in sea levels and rob. The climate change was significant effect on the reducing of cashew nut production. The rain that fell throughout the year in 2010 resulted in cashew production fell drastically, as in Wonogiri, Central Java (48.75 to 50.85%) and Muna, Southeast Sulawesi (93.63%). The impacts of climate change can be reduction  through the anticipation, adaption and mitigation. Anticipation performed by conducting assessment of agricultural resources, improvement of agricultural structure and infrastructure, imfrovement of  farming system and agribusiness, and management of socio-economi and cultural.  Technologi adaptation was done through the development of varieties tolerant to climate change and  the use of water saving technologies.  While migitation technology that can be applied are: planting cashew, cashew waste utilization, land management and use of organic fertilizers.